Karakteristik Susu Kerbau Sungai dan Rawa di Sumatera Utara - Evy Damayanthi; . Yopi; Hasanatun Hasinah; Triana Setyawardani; Heni Rizqiati; Salwa Putra (Jurnal Ilmu Pertanian Indonesia, 2014)
The objective of this research was to investigate the characteristics and differences in quality milk of Water andSwamp buffalo milk in North Sumatera. This research was conducted used complete random design used 30buffalo from three breeding farm in North Sumatera. Buffalo milk were collecting from lactating buffaloes on threetraditional farms located at Patumbak, Lubuk Pakam, and Siborong-borong with extensive farming system. Theresult of this research shown milk production per day for Swamp buffalo is 1 1.5 l and Water buffalo is 6 8 l withquality of Swamp and Water buffalo sequentially are for protein 5.14 ± 0.37% and 4.68 ± 0.41%, fat content 7.52 ±0.98% and 4.13 ± 0.73%, non-fat dry matter (NFDM) 10.61 ± 0.78% and 11.5 ± 0.86%, moisture 81.87 ± 2.26% and80.33 ± 2.33%, milk density 1.030 and 1.036, and then Total Plate Count (TPC) 3.79 x 106 and 5.08 x 105, shownindicated that there ware significant difference in protein, fat content and NFDM (P<0.01). But there is nodifferences in moisture and milk density. TPC shown that Swamp buffalo milk has above the maximum microbespresent in milk. The conclusion of this research is milk production of Swamp buffalo less than River buffalo but hashigher in chemical quality of milk than River buffalo such as protein, NFDM and fat content. Amino acids in Swampbuffalo milk were higher than River buffalo milk. Althought buffalo has less milk production than cow but buffalomilk were higher in all quality tested parameters and have more potential than dairy cow to be developed becausemaintenance of buffalo in North Sumatera is still use traditional method and not yet leading to efforts to obtainmaximum production performance.